New species of dung beetles (Coleoptera: Scarabaeidae: Scarabaeinae) from Costa Rica and Panama - Solís, Ángel; Kohlmann, Bert (Zootaxa, 2003)
The following new species of dung beetles (Coleoptera: Scarabaeidae) from Costa Rica and Panama are described: Copris tridentatus sp. nov., Onthophagus notiodes sp. nov., Onthophagus xiphias sp. nov. and Trichillum arcus sp. nov. Pedaridium bradyporum (Boucomont) is reported from the Pacific slope of Costa Rica for the first time. Drawings of the dorsal habitus of all species are provided.